Sosialisasi dan Workshop Pestisida Nabati Untuk Mengurangi Penggunaan Pestisida Kimia Di Desa Sipungguk Kecamatan Salo Kabupaten Kampar - Hermawan, Dadan; Suyanto, Suyanto; Affandi, Ridho; Anugrah, Aditya; Hafidza, Amanda; Nabila, Salsa; Suciarni, Anis Arum; Dzikra, Fahira Medina; Giawa, Jacob Immanuel; Ariashadi, Kania Putri; Rahma, Lulu Zulya; sabrina, sabrina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The socialization and workshop on botanical pesticide made from sungkai leaves (Peronema canescens) in Dusun I Teratak, Sipungguk Village, Salo District, Kampar Regency, aimed to reduce farmers’ dependence on chemical pesticides that negatively impact the environment and human health. Sungkai leaves were chosen for their bioactive compounds, such as flavonoids, tannins, saponins, and alkaloids, which effectively kill, repel, and inhibit pest development. The activity involved 22 farmers, the Head of BPP, and agricultural extension staff, and was conducted through material presentations, booklet distribution, Q&A sessions, and hands-on production of botanical pesticides. The results showed high community enthusiasm, with participants finding the method practical, eco friendly, and potentially a new business opportunity. This training not only improved technical skills but also raised awareness of sustainable agriculture based on locally available resources that are safe for humans and the environment.